Biologic therapy with anti-TNFa in rheumathoid atrhritis - G. Ferraccioli (PAGEPress Publications, 2011)
Objective: To evaluate the efficacy, the tolerability, and treatment survival of the association of anti-TNFa (Infliximab, Etanercept, Adalimumab) plus Methotrexate vs Methotrexate as monotherapy in patients with reumathoid arthritis (RA). Methods: Review of published controlled randomized clinical studies on the association of anti-TNFa plus Methotrexate vs Methotrexate alone in patients with rheumathoid arthritis (RA). Results in terms of remission and progression of radiologic damage, and clinical response expressed in terms of ACR 50 or ACR 70 were reviewed in the different studies. Results: In patients with RA the association of anti-TNFa plus Methotrexate led to a greater remission of radiologic damage and marked improvement of clinical response expressed as ACR 50 or ACR 70 compared to therapy with Methotrexate only. Conclusions: In the absence of controlled studies, review of the published studies showed that in RA patients the association of anti-TNFa plus Methotrexate is extremely more efficacious than therapy with Methotrexate only. Choice of the drug depends on the activity of the disease, the necessity of a fast response, the presence of side effects, the schedule of treatment and consequently the direct and indirect costs of the drug, and the easiness on supply and distribution.